2018
DOI: 10.1038/s41467-017-02615-9
|View full text |Cite
|
Sign up to set email alerts
|

Chronic alcohol exposure disrupts top-down control over basal ganglia action selection to produce habits

Abstract: Addiction involves a predominance of habitual control mediated through action selection processes in dorsal striatum. Research has largely focused on neural mechanisms mediating a proposed progression from ventral to dorsal lateral striatal control in addiction. However, over reliance on habit striatal processes may also arise from reduced cortical input to striatum, thereby disrupting executive control over action selection. Here, we identify novel mechanisms through which chronic intermittent ethanol exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
153
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(177 citation statements)
references
References 72 publications
14
153
2
Order By: Relevance
“…The rostral part of the ACC is implicated in error-related responses, including affective processing, and the caudal part of the ACC is associated with detection of conflict to recruit cognitive control 53 . Thus, reduction in inputs from prefrontal and cingulate cortices into striatum may disrupt the control over action selection 54 .…”
Section: Primary Outcome: Altered Brain Morphometry In Sudsmentioning
confidence: 99%
“…The rostral part of the ACC is implicated in error-related responses, including affective processing, and the caudal part of the ACC is associated with detection of conflict to recruit cognitive control 53 . Thus, reduction in inputs from prefrontal and cingulate cortices into striatum may disrupt the control over action selection 54 .…”
Section: Primary Outcome: Altered Brain Morphometry In Sudsmentioning
confidence: 99%
“…A transition from goal‐directed to habitual responding for drugs of abuse is thought to contribute to the compulsive patterns of drug‐seeking and taking that are characteristic of SUD (Barker & Taylor, ; Everitt & Robbins, ; Jentsch & Taylor, ; Ostlund & Balleine, ). Exposure to drugs of abuse including amphetamine, alcohol, or cannabis can engender faster formation of habits (Nazzaro et al., ; Nelson & Killcross, ; Renteria, Baltz, & Gremel, ). Identification of pharmacological tools that are able to reduce habitual and subsequently improve goal‐directed control of behavior would, therefore have substantial therapeutic benefit for disorders in which compulsive, habitual actions are a primary deficit.…”
Section: Introductionmentioning
confidence: 99%
“…After 7 weeks of intermittent access to 20% alcohol using a 2 bottle choice paradigm (IA20%2BC), high-drinking rats (alcohol intake >3.5 g/kg/24h) were trained to self-administer 20% alcohol in an operant self-administration (OSA) paradigm (34) with modification adapted from (20, 35,36).…”
Section: Habitual and Goal-directed Alcohol Seekingmentioning
confidence: 99%
“…The OFC sends projections to the dorsal striatum (DS), including the DLS (20). In addition, Renteria and colleagues showed that alcohol vapor exposure generated habitual behavior via the disruption of OFC to DMS circuit (36). Thus, it is plausible that mTORC1 activation is strengthening OFC projections to the DLS and or through weakening of OFC to DMS projection.…”
Section: Mtorc1 In the Ofc And Habitmentioning
confidence: 99%